Canciones infantiles y desarrollo del lenguaje oral en niños de la Institución Educativa Inicial N° 178 Lily Vásquez Ribeyro, Belén 2022 - Horna Yahuarcani, Karol Marjory (2024)
The research titled children's songs and oral language development in children from the Initial Educational Institution No. 178 Lily Vásquez Ribeyro, in the district of Belén in the city of Iquitos, 2022; developed a quantitative investigation, aimed at finding the relationship between the variables of study, focusing on a descriptive, correlational, non-experimental design, in a sample of 120 children selected by applying probabilistic sampling and applying data collection instruments focused on collecting information related to the study variables. The results presented in the report allow us to see the relationship between children's songs and the development of oral language. Because it enhances pronunciation, as well as the oral expression of words. The correlation statistic states that 0.750, using the scatterplot describes the points of a cloud with a positive linear trend. the Kolmogorov-Smirnov goodness of fit for the variables “children's songs” and “The development of oral language” with a probability < 0.05, rejecting the null presumption and accepting the alternative presumption, concluding that the variables do not fit the distribution normal and as a consequence the analysis of the theory will use non-parametric tests such as Spearman's rho for comparison, using the Student's t test statistic with n-2 degrees of freedom. Concluding the research in a statement that a union is observed between the study variables in the student population focused on and used for this research.